Transformation from Commercial Port to Industrial City: Discussion on Industrial Land-use Planning and Industrial Building Construction in Shanghai (1945-1960) - Li, Lingzhou; Peng, Nu; Zhang, Junjie (International Planning History Society Proceedings, 2022)
This paper compares the four urban plans of Shanghai especially the industrial land-use from 1940s to 1950s, and reveals the changes in the design and construction of industrial buildings with the development mode shifted from spontaneity to the planned. The paper points out that the establishment of socialist political and economic system and the positioning of Shanghai by the national industrialization strategy have completely changed the urban development in Shanghai, which in turn led to the spatial reformation of the industrial location in Shanghai during the transition from light industry to heavy industry in 1953-1957. It also contributes to the large-scale expansion of industrial land and development of suburban industrial areas and industrial satellite towns after 1958 and prompts the transformation of Shanghai into an industrial city. The urban spatial structure of Shanghai also changed from a mono-center structure with the original concession as the core to a poly-center structure with the industrial centers as the core. The adoption of the Soviet standards and norms in industrial buildings, the clear zoning of general layout, and a large number of large-scale, large-span factories have contributed to the important image of the development of heavy industry in Shanghai during this period.